How do we know what we don't know? Exploring Deaf people's experiences of supporting their Deaf family member living with dementia. (July 2020) - Ferguson-Coleman, Emma; Johnston, Alice; Young, Alys; Brown, Fiona; de Sainte Croix, Ruth; Redfern, Paul
Deaf sign language users living with dementia and their carers, some of whom are Deaf, routinely face everyday barriers in accessing information, support (both formal and informal) and services. The familial care situation is further complicated given that most Deaf people will choose a life partner who is Deaf and most Deaf couples will have hearing children. This study focussed specifically on the everyday experiences of Deaf carers and the impact of caring for a loved one with dementia. Drawing on data from a wider consultation about dementia care, three Deaf carers were directly interviewed in British Sign Language by a Deaf researcher about their everyday experiences of care, support, and services. Thematic analysis focussed on: access is more than the provision of interpreters; effective care for the carers; and unknowing risk taking. Findings demonstrate the multifaceted effects of barriers to knowledge and information when the care partner is also Deaf, the urgent need for effective support for Deaf carers and unrecognised safeguarding concerns that are a result of lack of access to forms of basic knowledge about living with someone with dementia and potential coping strategies. Nonetheless, the participants demonstrated novel solutions and resilience in the face of these multiple challenges. Implications are drawn for future targeted services to supported Deaf carers of people affected by dementia.